2012
DOI: 10.1039/c2dt11731b
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the copper coordination, electrochemistry, and Cu(ii) reduction kinetics of biologically relevant selone and thione compounds

Abstract: Selenium- and sulfur-containing compounds can act as antioxidants by binding copper. To determine how this copper coordination results in the observed antioxidant activity, biologically relevant Cu(+) and Cu(2+) complexes with the formulae [Cu(dmit)(3)](+) (3), [Cu(dmise)(4)](+) (4a), and [Tpm(iPr)Cu(MISeox)](2+) (6) (dmise = N,N'-dimethylimidazole selone; dmit = N,N'-dimethylimidazole thione; MISeox = bis(1-methylimidazolyl)diselenide; Tpm(iPr) = tris(1,3-diisopropylpyrazolyl)methane) were synthesized, charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 82 publications
2
47
0
Order By: Relevance
“…us, the Cu(II)(OSe) 2 /Cu(I)(OSeH) 3 + and Cu(II)(ESe) 2 /Cu(I)(E-SeH) 3 + redox couples are 0.17 V and 0.15 V more reducing than their respective sulfur analogues. While the sulfur compounds have the more positive potential and therefore suggests a greater protection from the recycling of Cu(I) to Cu(II) from past experiments into the binding of N,N′dimethylimidazole selone and N,N′-dimethylimidazole thione to Cu, similar differences in reduction potentials were observed [36,40]. In particular, the reduction potentials for the Cu(II)-selone complexes were more negative than the Cu(II)-thione analogues by an average of 0.11 V [36,40].…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…us, the Cu(II)(OSe) 2 /Cu(I)(OSeH) 3 + and Cu(II)(ESe) 2 /Cu(I)(E-SeH) 3 + redox couples are 0.17 V and 0.15 V more reducing than their respective sulfur analogues. While the sulfur compounds have the more positive potential and therefore suggests a greater protection from the recycling of Cu(I) to Cu(II) from past experiments into the binding of N,N′dimethylimidazole selone and N,N′-dimethylimidazole thione to Cu, similar differences in reduction potentials were observed [36,40]. In particular, the reduction potentials for the Cu(II)-selone complexes were more negative than the Cu(II)-thione analogues by an average of 0.11 V [36,40].…”
Section: Resultsmentioning
confidence: 70%
“…While the sulfur compounds have the more positive potential and therefore suggests a greater protection from the recycling of Cu(I) to Cu(II) from past experiments into the binding of N,N′dimethylimidazole selone and N,N′-dimethylimidazole thione to Cu, similar differences in reduction potentials were observed [36,40]. In particular, the reduction potentials for the Cu(II)-selone complexes were more negative than the Cu(II)-thione analogues by an average of 0.11 V [36,40]. While both the thione and selone prevented copper redox cycling and copper-mediated DNA damage, it was found that the selone did so where the reduction of Cu(II) to Cu(I) occurred 3x faster than in the presence of the thione [36].…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations